Development of RT h-CLAT, a Rapid Assessment Method for Skin Sensitizers Using THP-1 Cells as a Biosensor - Hiroki Koyama; Ayami Maeda; Peiqi Zhai; Keiichiro Koiwai; Kouichi Kurose (Biosensors)
In recent years, in vitro skin sensitization assays have been recommended as animal-free alternatives for the safety assessment of cosmetics and topical drugs, and these methods have been adopted in OECD test guidelines. However, existing assays remain complex and costly. To address this, we recently developed a more efficient, cost-effective, and accurate method for evaluating skin sensitizers by using immune cell-derived THP-1 cells as a biosensor, coupled with an RT-PCR-based assay. In this study, we further refined this method to enable even faster assessment of skin sensitization. By performing comprehensive RNA sequencing (RNA-Seq) analysis, we examined gene expression profiles induced by sensitizers in THP-1 cells to identify potential sensitization markers, ultimately selecting the optimal markers and conditions for evaluation. Our findings indicate that after exposing a test chemical to THP-1 cells for 5 h, measuring the expression levels of the JUN and HMOX1 genes via real-time PCR allows for a reliable assessment of sensitization. A test compound is defined as a sensitizer if either gene shows a more than two-fold increase in its expression compared to the control. Applying this improved method, designated as RT h-CLAT, we evaluated the sensitization potential of 43 chemicals. The results demonstrated higher accuracy compared to the human cell line activation test (h-CLAT) listed in the OECD guidelines, while also reducing the required assessment time from two days to one.